Pengembangan Aplikasi Point of Sale untuk Meningkatkan Kinerja Agen Softdrink Menggunakan Metode Prototype - Ayu Kusmawati; Wahyu Sri Utami (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Ice Gum Softdrink Agent is a company that provides softdrink stock to sellers. Currently, the sales system at the Ice Gum Softdrink Agent still uses a conventional system. The method of recording data at softdrink agents that is still manual in the process of monitoring and managing administrative data causes the data to be untidy and a lot of it is tucked away until it is lost, This will of course affect the transaction process and customer comfort during the transaction. To see the status of these issues requires developing a point of sale (POS) application. The existence of this system design will solve the problems taken in carrying out the transaction process and managing agent data starting from registration, monitoring, and product retrieval. As well as to overcome agent obstacles in data processing, stock processing, incoming or outgoing transaction processes to avoid accidental errors. The framework or system design in this study will be used with the prototype method The existing system framework in this research will be used with a prototype method that carries out direct observations at the Ice Gum Candy Agent in Pasuruan City to analyze problems, design a more detailed system design, namely by carrying out UML design, making program code, developing a database according to class diagrams. and system testing After the application design is complete, the next stage is testing using method is the black-box testing. The hope is that through the implementation of this application, it will be possible to implement and manage orders, manage sales data and stock of goods in a computerized and more effective manner